LORONG LITERASI GOWA PROGRAMS IN PACCINONGANG SUB DISTRICT - Kuncoro G. Pambayun; Rian Dwi Hapsari; Dzuljalali Dzuljalali (Indonesian Journal of Librarianship, 2020)
Problem Statement: The author focuses on the problem of low reading culture and the lack of awareness of the village community towards sub district literacy activities. Purpose: This study aims to know the participation of youth in the Lorong Literasi Gowa Programs in Paccinongang Sub District. Method: This study uses mixed methods. The technique of collecting data are done by survey (50 respondent), interviews (7 informant), and documentation. Result: The findings are youth participation in planning is adequate, implementation and utilization of results are quite good, although it is still constrained by the preoccupation of youth and the low level of awareness of some youth. Conclusion: Youth participation the Lorong Literasi Gowa Programs in Paccinongang Sub District has been going well because of the synergy of the local government and its youth community. In order to increase youth participation, it is recommended to optimize information technology, social media and collaborate with various components including entrepreneurs.